Penyelesaian Sengketa Hak Asuh Anak Setelah Perceraian: Perbandingan Antara Indonesia dan Inggris - Tiara Ananda Rahman; Wardani Rizkianti (Jurnal USM Law Review)
This research aims to compare child custody arrangements in Indonesian and English family law, as well as to analyze the prospects for joint custody in resolving child custody disputes in Indonesia. This research is motivated by the increasing number of divorce cases in Indonesia, as well as many children who are victims of problematic parenting and parental conflict. This research needs to be carried out because Indonesia does not have legislation that specifically and in detail regulates joint custody. This research can provide an understanding of the importance of child custody arrangements resulting from divorce. It can be a reference for changes or improvements to arrangements regarding child custody in Indonesia. This research examines child custody arrangements resulting from divorce in Indonesia and England, as well as the prospects for joint custody in Indonesia. This topic has not been explained comprehensively in previous research. This research uses normative legal research methods with a comparative approach and a statutory approach, as well as literature study data collection techniques. The results of this research show that there are differences regarding child custody arrangements in Indonesia and England. The similarity is that both countries, in deciding or determining matters relating to child care, prioritize the best interests of the child. Shared parenting is in line with the basic principles in Indonesian laws and regulations, namely the principle of the best interests of the child. Resolving child custody disputes can be done through mediation, where a divorced husband and wife agree to plan shared parenting for their children.